Dielectric spectroscopy and electrical conductivity measurements of a series of orthoconic antiferroelectric liquid crystalline esters. Issue 1 (2nd January 2021) - Nepal, Shantiram; Das, Banani; Das, Malay Kumar; Sarkar, Madhumita Das; Dabrowski, Roman
Abstract: Dielectric spectroscopic measurements of five homologous series of orthoconic antiferroelectric liquid crystalline (OAFLC) esters (S)-MHPOBC ((S)-4-(1-methylheptyloxy) carbonyl phenyl 4 ' -octyloxy-4-biphenylcarboxylate) has been investigated. The investigated compound contains SmC*, SmCA * and SmA phase with SmCA * phase at a broad temperature range. Parameters such as absorption curve, dispersion curve, Cole-Cole plot, relaxation frequency, relaxation time, dielectric strength and electrical conductivity has been discussed. The structure property correlations of these compounds are also highlighted in the light of the dielectric measurements. Compound S1.6 (FF) and S2.6 (FH) has dielectric strength of around 250 in the SmC* phase due to the presence of Goldstone mode.